The relevance of psycho-social theories in peace education and conflict resolution (2009)
Though conflict can cause distress, it is not an inevitable destructive and imposing barrier. Managing conflict is an essential life skill that is too often neglected. There is need to look at theories which can enhance conflict resolution through the adaptation of peace education. This paper sees peace education from three viewpoints: the environment in which the conflict occurs, the parties involved in the conflict and the process of arriving at the solution/ management of such conflict. It is against this background that this paper discusses the relevance of psycho-social theories to conflict resolution and peace education, The paper reviewed some theories such as psychodynamics, field theory, gaming theory and human relations theory as applicable to peace education and conflict resolution. The paper concludes that the content of peace education will lead to development of skills, attitude and knowledge which will guarantee peace and harmony within and between people and organizations and in all contextual application of the principle.